Skull shape and size variation within and between mendocinus and torquatus groups in the genus Ctenomys (Rodentia: Ctenomyidae) in chromosomal polymorphism context - Fornel, Rodrigo (2018)
We tested the association between chromosomal polymorphism and skull shape and size variation in two groups of the subterranean rodent Ctenomys. The hypothesis is based on the premise that chromosomal rearrangements in small populations, as it occurs in Ctenomys, produce reproductive isolation and allow the independent diversification of populations. The mendocinus group has species with low chromosomal diploid number variation (2n=46-48), while species from the torquatus group have a higher karyotype variation (2n=42-70). We analyzed the shape and size variation of skull and mandible by a geometric morphometric approach, with univariate and multivariate statistical analysis in 12 species from mendocinus and torquatus groups of the genus Ctenomys.We used 763 adult skulls in dorsal, ventral, and lateral views, and 515 mandibles in lateral view and 93 landmarks in four views. Although we expected more phenotypic variation in the torquatus than the mendocinus group, our results rejected the hypothesis of an association between chromosomal polymorphism and skull shape and size variation. Moreover, the torquatus group did not show more variation than mendocinus. Habitat heterogeneity associated to biomechanical constraints and other factors like geography, phylogeny, and demography, may affect skull morphological evolution in Ctenomys.